Ultra Petita dalam Pengujian Undang-Undang oleh Mahkamah Konstitusi - Suwarno Abadi (Jurnal Konstitusi, 2015)
Ultra petita decision practiced under the MK’s jurisdiction to review the constitutionality of legislation needs to be assessed carefully. This practice should not be condemned as illegitimate because there is no explicit constitutional rule that guarantee it. The author therefore argues that this practice can be justified under two reasons. First, judicial activism. Second, the very nature of constitutional adjudication in order to defend the supremacy of the constitution over legislation. According to these reasons, the MK’s ultra petita decision should be upheld because this practice is the most reasonable means to protect the constitution.